كسرة همزة "إن" فى القرآن الكريم سورتي البقرة والقصص - Ari Khairurrijal Fahmi (Al-Ma‘rifah, 2017)
The objective of this research is to acquire deep understanding of the "kasrah hamzah inna" on the al-Quran al-karim, al-Baqarah and al-Qasas epistles,  which consist of 149 verses. The research method used in this study is a descriptive qualitative method using content analysis of the verses of Quran. The result showed that there are 97% the "kasrah" was compulsory, and 3% was uncompulsory. The most verses appear with "inna" is in the beginning of the kalimah, and after the verb "Qaul". The 97% of  kasratu inna is a compulsory, its divided into five: (1) At the beginning of the sentence amounted to 80 (54%) (and it is divided into 5; hakikat it was 13 (16%), hukm it was  3 (4%), ibtida'iyah it was  12 (15%), isti'nafiyyah it was 12 (15%), ta'liliyyah 40 (50%). (2) After the Conjunction it was 1 (1%). (3) After the answer of  oath sentence  it was  1 (1%). (4) After the words amounted to 31 (21%). (5) After the sentence torch circumstances it was 5 (4%). Meanwhile, the position of non compulsory kasratu hamzah inna was founden  after faa aljazaa, only 5 times (3%). The results show  that many types of kasrah hamzah inna was founded in al-Baqarah and al-Qasas.